If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9c*3=6
We simplify the equation to the form, which is simple to understand
9c*3=6
Simplifying:
+27c=6
We move all terms containing c to the left and all other terms to the right.
+27c=+6
We simplify left and right side of the equation.
+27c=+6
We divide both sides of the equation by 27 to get c.
c=0.222222222222
| 49x^3-56x^2+16x=0 | | (5y^2-7y+3)+(-2y^2+4y+1)= | | 6p+4=2(2p+1) | | 10x+23(x-5)=182 | | 4(2x+1)=3(x+13) | | 12x^3+23x-24=0 | | 3.5b-33.4=75.5 | | 14p-10=8+2p | | 2g+14+5g=8-3+8 | | 12x-6=2x+7 | | 3(2x-1)+4=x+25 | | 14x-48=5x-3 | | 18-4x=7x-7 | | 2y-80=y+9 | | 2y-80=y+90 | | 10x-24=8x+12 | | X+30=2x | | 4[2x-5(x-3)]=6 | | 10-4x=6-2x | | 36+340=2 | | 7x(2)+x-8=0 | | 9x(x-2)=9x^2+40 | | 6w-14w=-72 | | -7(x+4)-11=16+8 | | 3(2x-5)+9=12 | | 20n=m | | m=20n | | 2x-2y+z=7 | | x-4-13x-2+36=0 | | x^2-16x-29=0 | | (11b-8)-5(2b+4)=-6 | | 9m=7 |